Pendampingan Metode Tilawati dalam Melafazkan Huruf Hijaiyah untuk Meningkatkan Kemampuan Membaca Al-Qur’an di TPA Darul Hikmah Barito Utara Desa Walur: Studi Pengabdian Masyarakat - udin, rizal saprudin; Jumrodah; Yosrizal Wahpiudin; Muhammad Facrurozi; Muhammad Miftahul Khoir; Ahmad Sairaji; Feni Maulidia Saputri (Jurnal Makkareso, 2023)
One method for reading the Koran is the tilawati and iqro methods, while the one that is familiar to the North Barito community is the iqro method. The aim of this research is to improve the quality of reading the Al-Qur'an by applying the tilawati method, in KKN community service in the village of Walur Barito Utara, researchers found problems of a religious nature at the Darul Hikmah TPA in Walur village. This village has a population of 683 people, all of whom are Muslim. The core problem point found was that the subject was less able to recognize hijaiyah letters fluently and was confused in differentiating letters that were almost similar in terms of pronunciation and shape and was less able to read hijaiyah letters in sequence fluently. Apart from the problems above, the subject also did not want the material to be repeated from volumes 1, 2 and 3 on the pretext that the students had already reached volumes 4, 5 and 6 in the previous lesson. The method used to overcome the above problem is by collaborating two methods at once in each KBM TPA Darul Hikmah Walur village. The service method adopted is using a qualitative descriptive PAR type of community service. Based on the results of this service, it can be concluded that mentoring with the tilawati method can have an impact on the quality of iqro' reading, thereby improving the ability to read the Al-Qur'an among students at TPA Darul Hikmah.